Vitamin D analyses in veterinary feeds by gas chromatography-tandem mass spectrometry. Issue 1 (February 2021) - Lehner, Andreas; Johnson, Margaret; Zimmerman, Alan; Zyskowski, Justin; Buchweitz, John
This report examines the feasibility of determination of Vitamin D3, D2 and their 25-hydroxy metabolites utilizing Gas Chromatography Tandem Mass Spectrometry (GC/MS/MS) as a potential alternative to popular Liquid Chromatography Tandem Mass Spectrometric (LC/MS/MS) methodologies. The GC/MS/MS approach was found to operate reasonably well despite long-standing concerns that gas-liquid chromatography of vitamin D compounds invoke thermal rearrangements owing to the relatively high inlet and capillary column temperatures used. The workup procedure involved incubation of feed samples with concentrated potassium hydroxide for overnight fat saponification, extraction of D Vitamins in n-hexane and reaction with N, O-bis(trimethylsilyl)trifluoroacetamide at 70 °C for 30 mins. In addition to parent compounds, small amounts of pyro-, isopyro-, and iso-vitamin D and isotachysterol3 variants were obtained from each Vitamin D-related compound upon extraction and GC/MS/MS analysis. Mass spectral and chromatographic behavior of these compounds are herein described and interpreted. Multiple Reaction Monitoring settings on GC/MS/MS included m/z 456→351 for Vitamin D3 and m/z 486→363 for Vitamin D2. Trimethylsilylation enabled single predominant peaks for Vitamins D3 and D2, and sample workup in the presence of deuterated Vitamin D analogs enabled accurate and precise sensitivity to 1 ppb (ng/g) in feeds. The method could be extended with reasonable accuracy to 25-hydroxy (25OH) compounds, but accuracies would be significantly improved by inclusion of respective 25OH-specific deuterated internal standards. The method was applied to 27 submissions of suspect dog foods of which 22% were discovered elevated and 44% were discovered to contain toxic levels of Vitamin D3. The described method was thus discovered to provide a suitable mass spectrometric approach for Vitamin D, proving itself here specifically of value in detection of ergocalciferol and cholecalciferol in animal feeds. The specificity and sensitivity of the tandem quadrupole approach can enable suitable applicability to serum determination if desired.